A Review on Hydrogels - Sharma, Sunil; Goutam, Shubham; Nama, Nitin; Khinchi, M. P.; Singh, S. P. (Asian Journal of Pharmaceutical Research and Development, 2017)
Hydrogels are three-dimensional, hydrophilic, polymericnetworks capable of absorbing large amounts of water orbiological fluids.Today, drug delivery experience several challenges where hydrogel could be one potential answer to those.Hydrogels are of particular interest for drug delivery applications due to their ability to address these needs in addition to their good biocompatibility, tunable network structure to control the diffusion of drugs and, tunable affinity for drugs. Hydrogels are also limited for drug delivery applications due to the often quick elution of drug from their highly swollen polymer matrices as well as the difficulty inherent in the injection of macroscopic hydrogels into the body. The hydrogels have been used extensively invarious biomedical applications, viz. drug delivery, cell carriers and/or entrapment, wound management and tissue engineering. They have started to create a niche in severalfields of medicine like in specific site drug delivery, tissue reconstruction and tissue engineering and even as biosensors.In this review article an attempt has been made to explain the properties of hydrogels, their methods of preparation and its applications.